Pemerolehan Bahasa Pada Anak Berkebutuhan Khusus Di SLB Martapura OKU Timur - Sugiarti Sugiarti; Herni Fitriani (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
Language acquisition or language acquisition is a process that takes place in the brain of a child when he gets his first language or mother tongue which means acquisition of language regarding his first language. Normal human brain functions and speech tools can certainly speak well. Similarly, mentally disabled children also need language to communicate or to voice their hearts to others. However, the intellectual capacity of mentally retarded children who are below the average makes them difficult to obtain language and they often experience interference in language. Language is very important for everyone to master. With language, humans can convey their thoughts and feelings to others and can capture and understand the symbols of others. Language acquisition is closely related to children's cognitive development, therefore language skills (linguistic abilities) will be in accordance with their cognitive abilities, because linguistic abilities are one of the main factors that can influence a child's success in mastering language. But as is well known that autistic children have cognitive barriers that also cause language development is also hampered. These obstacles can be seen from the imbalance of language development with the age of the calendar (cronolicalage). Nevertheless they also have the same rights as normal children to obtain language as a tool to communicate with their environment.